Performing Devotion: Belief, the Body, and the Book of Common Prayer 1775–1840 - Laura Davies (Humanities, 2018)
This article examines three texts published between 1775 and 1840 that attempt to model an ideal reading of the Anglican liturgy and to render it on the printed page, exploring the ways in which elocutionary instruction, acting theory and accounts of public worship intersect within them through the figures of inscription and incorporation. Reflecting on the choice of the famous actor David Garrick as an exemplary reader in the two later texts, and drawing on the work of Jacques Derrida and Judith Butler, it discusses how and why these texts attempt to regulate competing ideas regarding the concepts of performance, embodiment, and assembly. The argument is made that although prescriptive in their demands, to varying degrees these texts acknowledge their own insufficiencies, and recognise not merely the difficulty of the task of transposing oral performance to a series of textual signs, or of accounting for the nature of devout worship, but also a more fundamental excess and irreducibility in the constitution of the self.